Pasireotide‐induced hyperglycemia in a patient with Cushing's disease: Potential use of sodium‐glucose cotransporter 2 inhibitor and glucagon‐like peptide‐1 receptor agonist for treatment. Issue 12 (13th August 2020) - Shikata, Masato; Ashida, Kenji; Goto, Yuka; Nagayama, Ayako; Iwata, Shimpei; Yano, Mamiko; Hasuzawa, Nao; Hara, Kento; Mawatari, Kazutoshi; Sakata, Kiyohiko; Tsuruta, Munehisa; Wada, Nobuhiko; et al.
Abstract: Pasireotide improves hypercortisolemia and induces hyperglycemia via somatostatin receptor type‐5 stimulation. GLP‐1RA and SGLT2 inhibitor potentially help regulate hyperglycemia in patients with Cushing's disease, especially after pasireotide administration. Abstract : Pasireotide improves hypercortisolemia and induces hyperglycemia via somatostatin receptor type‐5 stimulation. GLP‐1RA and SGLT2 inhibitor potentially help regulate hyperglycemia in patients with Cushing's disease, especially after pasireotide administration.